Improvements of detection sensitivity in capillary electrophoresis (CE) for Peptides - Mohd Hazzar Johari (2008)
Improvements of detection sensitivity in capillary electrophoresis (CE) for Peptides Application of CE to peptide samples is limited due to poor concentration limit of detection (CLOD). At very low concentration, peptide is undetectable by CE with UV absorption detection. The lack of detection sensitivity of CE occurs as a result of small sample volume mean limiting loading capacity and short optical path length for detection. The main objective of this project is to analyze two preconcentration techniques that is sample stacking and field-enhanced sample injection in improving detection sensitivity of CE for peptide analysis. The second objective is to compare these two techniques and determine which technique is more effective in improving the detection sensitivity of CEo In sample stacking, peptides were prepared in 100% (v/v), 50% (v/v), 40% (v/v), 30% (v/v), 20% (v/v) and 10% (v/v) of phosphate buffer while BGE is always 100% (v/v) of phosphate buffer. The result shows significant increase in value of peak height gradually from 1000/0 (v/v) to 10% (v/v) phosphate buffer. The best result for sample stacking was obtained when peptides were prepared in 10% (v/v) phosphate buffer. FESI use the same concept as sample stacking but differ in term of the injection procedure and focusing process. The best result for FESI was obtained when peptides were prepared in 20% (v/v) phosphate buffer. In 10% (v/v) phosphate buffer, only 8 peptides were detected instead of 9. The lost peptide was identified as methionine enkephalin. Injection of short plug of dilute buffer before injecting peptides in FESI ensures amplified field thus produce higher peaks. For comparison, FESI is more effective in improving detection sensitivity of CE in peptide analysis based on high significant peak that can be observed from e1ectropherogram compared to sample stacking. As conclusion, the aim of this project has successfully been achieved.